Internalisasi Nilai Keadilan dan Kesetaraan Gender dalam Hukum Keluarga Islam (Sebuah Strategi Pembangunan Indonesia Emas Berkelanjutan 2045) - Firqah Annajiyah Mansyuroh; A Hashfi Luthfi (Fakultas Syariah dan Ekonomi Islam, 2022)
In line with Indonesia's Golden Vision 2045, many aspects must be considered, including gender equality and awareness. Until now, the level of gender equality in Indonesia is still low. Islam is often the scapegoat in the issue of gender equality in the family and society in Indonesia. Whereas in the Compilation of Islamic Law it is clear that the values of justice and gender equality should be the reference for Indonesian society. This paper wants to explain that the internalization of the values of justice and gender equality in Islamic family law can be one of the development strategies of Indonesia Gold for Sustainable 2045. It can be concluded that KHI is sufficient to show equality between men and women in family life and apply it in everyday life, becoming the key to Indonesia's development.